Relining efficiency and liner design for improved plant performance. (November 2015) - Yahyaei, M.; Powell, M.S.; Toor, Paul; Tuxford, Andrew; Limpus, Andrew
Graphical abstract: Highlights: Designing liners for efficiency through incorporating performance of relining. Relining efficiency will play a significant role in liner design. Benefits of designing liners for efficiency for the industrial case. Abstract: Liners in grinding mills not only protect the mill shell from the aggressive environment inside the mill, but they also play a significant role in the efficiency of grinding. The design of mill liners dictates the charge trajectory and hence the grinding efficiency. The common approach in designing liners is designing for a longer life. However, this approach does not necessarily consider optimum performance over the liner life. It has been observed in many operations that mills under-perform over a significant portion of the liner life (10–25% of the liner life at the beginning and often 5–10% at the end). This paper extends the method proposed by Toor (2013) and Toor et al. (2013) to design liners for performance through investigating the effect of relining efficiency using such an approach in an industrial case. As indicated in the Toor et al. (2013) study, relining efficiency affects the benefits that can be realised by designing liners for efficiency. Russell Mineral Equipment's Mill Reline Director (MRD) analyses the relining process and provides an accurate estimation of relining time for a given scenario. In this study, five different relining scenarios were simulated and compared against the reference reline (i.e. current liner design) to accurately estimate the time required for relining. This is the first study to demonstrate that incorporating relining constraints in the liner design can be used to inform liner design characteristics of a proper design that meets the requirements of an efficient relining practice. JKSimMet simulation for the industrial case predicts a liner which has same lifter face angle as the current liner design with reduced lifter height from 300 mm to 210 mm, could increase the plant throughput by 8% on average while producing a product with same P80 as the current liner. Considering relining time predictions by MRD for the proposed liner, this study predicts a 3.7% increase on average in throughput per annum. Although the proposed strategy will increase the cost of liners plus relining by 31.5% (i.e. A 548, 000), the increase in plant throughput is estimated to yield A 20.1 M of additional revenue based on data for 12 months to 30 June 2014 from the plant quarterly report.